Cellular Origins of the Lymphatic Endothelium: Implications for Cancer Lymphangiogenesis - Gutierrez-Miranda, Laura; Yaniv, Karina (Frontiers in Physiology, 2020)
The lymphatic system plays important roles in physiological and pathological conditions. In tumors in particular, lymphangiogenesis correlates with the presence of lymphatic metastasis, increased severity and poor prognosis. Therefore, a profound understanding of the cellular and molecular mechanisms underlying lymphatic vessel formation is required in order to improve current strategies for controlling malignant spread. Data accumulated over the last decades have led to a controversy regarding the cellular sources of tumor-associated lymphatic vessels and the putative contribution of non-endothelial cells to this process. Although it is widely accepted that lymphatic endothelial cells (LECs) arise mainly from pre-existing lymphatic vessels, additional contribution from bone marrow-derived cells, myeloid precursors and terminally differentiated macrophages, has also been claimed. Here, we review recent findings describing new origins for LECs during embryonic development and discuss their relevance to cancer lymphangiogenesis.